CP-100 Pegylated interferon ALFA 2-A in myeloproliferative neoplasms. (25th February 2017) - Scaldaferri, M; Varese, A; Tonelli, M; Barilà, D; Bianco, A; Valinotti, G; Caiazza, E; Martinetto, D; Ferroni, M; Cattel, F
Abstract : Background: Polycythaemia vera (PV), essential thrombocythemia (TE) and myelofibrosis (MF) are myeloproliferative neoplasms (MPN), characterised by a number of mutations related to proliferation and differentiation of myeloid cell lines. Peg-interferon α2a (P-IFN) is considered a promising option for the therapy of these pathologies, although in Italy this is an off-label use, as an alternative to hydroxyurea. Purpose: Evaluation of the therapeutic efficacy and tolerability of P-IFN in a cohort of PV, TE and MF patients treated according to an off-label protocol. Material and methods: The analysis consisted of review of the medical records of all patients with a diagnosis of PV, TE or MF, who were treated with P-IFN since 2010. Results: 38 patients were treated with P-IFN for MPN. 30 patients (79%) had a diagnosis of PV and 81.5% were positive for the JAK2 mutation; 89.5% of patients were undergoing phlebotomy treatment. P-IFN was used as firstline therapy in 21.00% of patients; the remaining 79% of patients previously received other treatments, mainly hydroxyurea (96.5% of previously treated patients). P-IFN was started because of the young age of patients (13.1%), to ameliorate the quality of life of patients (13.1%) or because of lack of response to previous treatments. Doses of P-IFN ranged from 45 μg/week to 145 μg/week. 12 patients (31.6%) stopped treatment; in 8 cases this was due to toxicity, in 2 cases to lack to efficacy and in 2 cases to toxicity and lack of efficacy. For 19 patients, P-IFN treatment elicited a clinical response, in terms of relief from constitutional symptoms and reduction of phlebotomy frequency, or a laboratory response, in terms of reduction of allelic load for the JAK2 mutation. 3 patients did not experience a response to treatment and for the other patient this evaluation is currently premature. Conclusion: Our data confirmed the efficacy and tolerability of P-IFN. Our study has some limits, due to the small number of patients and to their heterogeneity. Further data collection is needed to confirm these preliminary data, together with a cost-efficacy evaluation. References and/or acknowledgements: Pai SG, Kaplan JB, Giles FJ. Long-acting interferon for myeloproliferative neoplasms—an update. Expert Rev Hematol2016;9:915–7. doi:10.1080/17474086.2016.1231571. Epub 2016 Sep 13. No conflict of interest